AI-generated cancer prevention influencers can target risk groups on social media at low cost - Winterstein, Jana Therés; Abels, Julia; Kühn, Arlene; Carl, Nicolas; Wies, Christoph; Brinker, Titus Josef (European journal of cancer, 2025)
Background - This study explores the potential of Artificial Intelligence (AI)-generated social media influencers to disseminate cancer prevention messages. Utilizing a Generative AI (GenAI) application, we created a virtual persona, "Wanda", to promote cancer awareness on Instagram. - Methods - We created five posts, addressing the five most modifiable risk factors for cancer: tobacco consumption, unhealthy diet, sun exposure, alcohol consumption, and Human Papillomavirus (HPV) infection. To amplify the campaign's reach, posts were boosted using a custom-targeted as well as an automated advertisement algorithm. An overall budget of €100 was equally distributed between the two algorithms. Campaign performance was assessed based on the number of users reached and the age distribution of the audience. - Results - The campaign achieved a total of 9902 recognitions, with a cost-efficiency analysis revealing an average expenditure of €0.013 per reach. The most economical intervention achieved a cost of only €0.006 per reach. In comparing the two advertisement strategies, we observed similar overall reach but noted differences in the age demographics of the audience. - Conclusion - Our findings underscore the potential of combining generative AI with strategically targeted advertisement to promote cancer prevention messages effectively, with minimal time and financial investment. We discuss chances presented by GenAI applications in health communication, their implication, and the impact of parasocial relationships on content perception. This study highlights the potential of AI-driven influencers as scalable tools for digital health communication.
Gesehen am 13.08.2025